Membership Study of Open Cluster NGC 6134 using HDBSCAN Clustering Algorithm - Yusuf, M; Ramadhan, D G; Jatmiko, A T P; Perhati, T; Ramadhan, S; Arwinata, H I; Yap, F; Satya, L; Mandey, D; Arifyanto, M I; Premadi, P W (Journal of physics. Conference series, 2024)
We present the results of our study on the membership of open star clusters in the southern hemisphere, NGC 6134. The position of NGC 6134 is located near the galaxy’s plane, so the apparent position in the sky is in an area with high stellar density. This poses a challenge in distinguishing between cluster member stars and field stars. For this purpose, we use the Hierarchical Density-Based Spatial Clustering of Applications with Noise (HDBSCAN) algorithm on astrometric data from Gaia Data Release 3 (DR3). We take stars as samples up to a distance of 90 parsecs from the cluster’s center as membership determination samples. The spatial scope of this sample is intentionally larger than previous studies on this star cluster, as some recent membership studies have concluded that the size of star clusters turns out to be larger than what has been reported. The results of our study produced a consistent number of members with the results of other studies with the same sample size. The clustering algorithm was then performed multiple times using different values of the radius sample. We determined that NGC 6134 has 888 members (membership probability ≥ 0.5), with a radius of 30 parsecs from the cluster’s center.